Information technology quality management process of growing semiconductor single crystals - Шевченко, Игорь Васильевич (Eastern-European Journal of Enterprise Technologies, 2014)
A complex of information technologies for quality management of growing semiconductor single crystals is developed. The complex includes information technology for temperature field monitoring, information technology for operational decision support on the growing mode correction and information technology for optimizing geometrical parameters of the heat shield of growth setup. Growing semiconductor single crystals in most cases is carried out by the Czochralski method. Growing process is a complex combination of thermal and mechanical phenomena and is characterized by nonstationarity. Therefore, using stabilization and program management systems does not guarantee the process stability. Control over axial and radial temperature gradients in the ingot and the crystallization front zone is necessary. However, existing growing control methods and systems do not allow to realize these functions. The proposed information technologies implement indirect measurement of parameters of temperature fields in the melt and the ingot. This allows timely identify adverse situations and give recommendations for their elimination. In addition, it became possible to optimize the heat shield size and position in the ingot cooling zone. Implementing information technologies has allowed to reduce losses from the growing process failure and the cost of experimental works on selecting the geometric parameters of heat shields.